Scientific Exchange On Pediatric Strategies Enhancing Adolescent Emotional Intelligence, Academic Engagement, And Social Development Outcomes Today - Boregowda, Vinay Kumar Sadolalu; Verma, Seema; Karanjkar, Dr M N; Mohapatra, Ms. Sarita; Singh, Ranjana; Karanjkar, Dr M N; Parmar, Priyanka; Subramanian, Mohanraj (Adolescência e Saúde, 2026)
Adolescence is a very crucial phase of development, which involves fundamental emotional, academic, and social alterations, which become determinants of long-term health and well being. The role of pediatric strategies targeted at assisting adolescents has been attracting more and more attention because of the possibility of emotional intelligence development, academic interests improvement, and positive social growth support. The insights into the viability of this type of strategies is important in the process of creating interventions that would meet the needs of young people in a multifaceted manner. The aim of the study was to investigate the effects of pediatric strategies on the teenage emotional intelligence, academic engagement, and social development outcomes with the particular focus on Emotional Intelligence Score (EIS) as the main measure of evaluation. The used quantitative research design was cross-sectional that comprised adolescents aged between 12 and 18 years. Standardized questionnaires on the implementation of pediatric strategies, emotional intelligence, academic engagement, and social development were used to collect data. The main outcome measure was the Emotional Intelligence Score. To test the relationships between variables of the study and identify the effect of the pediatric strategies on the adolescent outcomes, descriptive statistics, reliability analysis, Pearson correlation analysis, and multiple regression analysis were performed. The results showed that teenagers that were subjected to effective pediatric strategies had higher scores on Emotional Intelligence, better academic participation, and better outcomes on social development. There were significant positive relationships between emotional intelligence, academic engagement and social development. Regression analysis also indicated that pediatric strategies were also important predictors of emotional intelligence and other developmental outcomes. The use of pediatric approaches is crucial in enhancing emotional intelligence and positive academic and social growth in adolescents. Combining specific pediatric therapies in healthcare, school, and family can help achieve better adolescent health and developmental outcomes.